INNOVATIVE METHODS OF TEACHING FOREIGN LANGUAGES IN SECONDARY EDUCATION IN UKRAINE - Ніна Нікольська (National Academy of Educational Sciences of Ukraine, 2022)
The main tasks were determined: the study of innovative methods of teaching foreign languages involved a theoretical analysis of the domestic pedagogical experience; essential characteristics of the main concepts in the investigated problem context are carried out. The article analyzes the meaning of the terms "bilingual education" and "immersion education" This approach is not new, its varieties have been used to study non-linguistic subjects for centuries, and today it is considered an effective way of forming bilingualism. Nowadays, students' native language is also used during education, so this approach has different names, such as "immersion education" or "bilingual teaching of subjects". Teaching in two languages is quite common in European countries. As a rule, such training does not require artificial encouragement, as it contributes to the expansion of the general horizons of students through familiarization with the peculiarities of foreign culture, forms a tolerant attitude towards the views, cultural characteristics of another representative of culture, related to national specificity. This process stimulates the need for further self-education and self-development, and is a necessary condition for professional work in the modern world.